2020
DOI: 10.3389/fpsyg.2020.02111
|View full text |Cite
|
Sign up to set email alerts
|

Referent Cueing, Position, and Animacy as Accessibility Factors in Visually Situated Sentence Production

Abstract: Speakers' readiness to describe event scenes using active or passive constructions has previously been attributed-among other factors-to the accessibility of referents. While most research has highlighted the accessibility of agents, the present study examines whether patients' accessibility can be modulated by means of visual preview of the patient character (derived accessibility), as well as by manipulating the animacy status of patients (inherent accessibility). Crucially, we also examined whether effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 31 publications
(106 reference statements)
7
11
0
Order By: Relevance
“…Although visual cueing was effective and directed our participants' gaze to the patient of an event scene, this manipulation of attention did not lead to a higher rate of non-canonical structures, confirming previous research that has found speakers of German to be disinclined to produce passives or OVS actives in event descriptions (Esaulova et al 2019(Esaulova et al , 2020. The aim of our study was to find out if this cross-linguistic difference in the propensity to produce noncanonical structures was related to morphological case marking.…”
Section: Discussionsupporting
confidence: 81%
“…Although visual cueing was effective and directed our participants' gaze to the patient of an event scene, this manipulation of attention did not lead to a higher rate of non-canonical structures, confirming previous research that has found speakers of German to be disinclined to produce passives or OVS actives in event descriptions (Esaulova et al 2019(Esaulova et al , 2020. The aim of our study was to find out if this cross-linguistic difference in the propensity to produce noncanonical structures was related to morphological case marking.…”
Section: Discussionsupporting
confidence: 81%
“…Averaged across cue positions (patient and agent), this resulted in an increase of around 5%. Similarly, Esaulova et al (2020) reported a significant increase of passives for patient-left relative to agentleft scenes of around 4% for German. Altogether, previous studies that took the position of the agent relative to the patient into account demonstrate that the position of agent and patient in transitive event scenes can affect the planning of a verbal description.…”
Section: Agent and Patient Positionmentioning
confidence: 91%
“…( Although all three structures are viable in German, previous production studies (Esaulova et al, 2019(Esaulova et al, , 2020Esaulova, Dolscheid, Reuters et al, 2021;Sauppe, 2017aSauppe, , 2017bSchlenter et al, 2022) have consistently shown that German speakers have a strong preference for canonical active SVO sentences when describing transitive event scenes. If they produce a non-canonical structure, German speakers produce passives rather than active OVS sentences (for more discussion, see Schlenter et al, 2022).…”
Section: Main Experiment: Scene Description Taskmentioning
confidence: 99%
See 2 more Smart Citations